Euclea divinorum Hiern: chemical profiling of the leaf extract and its antioxidant activity in silico, in vitro and in Caenorhabditis elegans model - Bogari, Hanin A.; Rashied, Rasha M. H.; Abdelfattah, Mohamed A. O.; Malatani, Rania T.; Khinkar, Roaa M.; Hareeri, Rawan H.; Wink, Michael; Sobeh, Mansour (Metabolites, 2022)
Euclea divinorum Hiern is a medicinal plant widely distributed in the northeast parts of South Africa. This plant has been used to treat miscarriage and to alleviate gastrointestinal problems. It can also be used externally for the treatment of ulcers and gonorrhea. In this study, we investigated the phytochemical composition of E. divinorum leaf extract using LC-MS and explored its antioxidant properties in vitro and in vivo. The total polyphenolic content of the extract was determined by the Folin-Ciocalteu method. DPPH and FRAP assays were employed to confirm the plant’s antioxidant potential in vitro. A survival assay in the Caenorhabditis elegans model was used to evaluate the extract’s ability to counteract juglone-induced oxidative stress. Moreover, a docking study was performed for the extract’s metabolites, in order to predict possible molecular targets that could explain the antioxidant effect of the plant on a molecular level. This in silico approach was accomplished on three different proteins; xanthine oxidase enzyme, heat shock protein 90 (Hsp90), and induced nitric oxide synthase (iNOS). Docking scores of the resulting poses and their interactions with binding sites’ residues were explored for each protein and were compared to those of simultaneously docked respective co-crystallized and reference substrates. The extract furnished promising antioxidant activities in vitro and in vivo in the C. elegans model that might be attributed to the presence of 46 compounds, which showed several interactions and low binding scores with the tested enzymes. In conclusion, E. divinorum is a promising, safe, and effective antioxidant candidate that could be used to ameliorate oxidative stress-related disorders.
Gesehen am 20.01.2023